Harvest - Markham, Lois. (Woodbridge, Conn. : Blackbirch Press, 1999)
Describes how people in various countries around the world give thanks for the harvest.
Includes bibliographical references (p. [24]) and index.
L.A. Recommended Foreign Language.
6.8.
6.8
3-6
Keywords: Harvest festivals -- Juvenile literature; Festivals; Harvest festivals; Holidays; Festivals; Harvest festivals; Holidays